INTEGRATION OF CONSTRUCTION AND AGRICULTURAL TECHNOLOGY: UTILIZATION OF HYDROPONIC GARDENING SYSTEM FOR ALTERNATIVE FOOD PRODUCTION - Arcadio, Redjie D; Umbay, Ninna Ysabella N (Journal of Agriculture and Technology Management, 2022)
This project aims to design and construct a hydroponic system that is fully utilized that can be integrated into the agricultural and construction technology curriculum while introducing entrepreneurial skills all the same. The hydroponic gardening system is another means of the food-producing system through agriculture that doesn’t require a significant area of land. On the other hand, this gardening system does not need heavy soil cultivation but instead integrates construction technology through its structure. It is easy to manage by women and can be set up in a little area in the front or backyard of each household. This type of agricultural system can somehow augment the needs of every family since men are not usually needed for this gardening system and they can freely perform their every duty in their respective companies while left in the care of wives. Therefore, it is recommended to fabricate the hydroponics gardening system and share the technology with another municipality not for household use but for entrepreneurial purposes.